2018
DOI: 10.1039/c8ta00533h
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids as an efficient medium for the mechanochemical synthesis of α-AlH3 nano-composites

Abstract: Aluminum hydride (AlH3) is one of the most promising hydrogen storage materials that has a high theoretical hydrogen storage capacity (10.08 wt%) and relatively low dehydriding temperature (100–200 °C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…Similar studies can be found in recent References [58][59][60][61]. Due to the complexity of the structural information and the electronic structures of the periodic table elements [62][63][64][65][66][67][68][69][70][71], a challenge of their data-mining is the definition of suitable descriptors as the model inputs. In the past decades, there was a large number of descriptors that have been applied for the machine learning process of chemical and materials systems, such as bond length, bond angle, and group contribution analysis [72].…”
Section: Mining the Trends And Properties In Chemistry And Materialssupporting
confidence: 61%
“…Similar studies can be found in recent References [58][59][60][61]. Due to the complexity of the structural information and the electronic structures of the periodic table elements [62][63][64][65][66][67][68][69][70][71], a challenge of their data-mining is the definition of suitable descriptors as the model inputs. In the past decades, there was a large number of descriptors that have been applied for the machine learning process of chemical and materials systems, such as bond length, bond angle, and group contribution analysis [72].…”
Section: Mining the Trends And Properties In Chemistry And Materialssupporting
confidence: 61%
“…These features enable ionic liquid to regulate the activity and selectivity of catalysts. Owing to its unique properties, the ionic liquid is used in chemical research as a solvent for various types of reactions, [12][13][14][15][16] extractant in separation/purication, [17][18][19][20] and has applications in the eld of electrochemistry. [21][22][23] Zhao et al have reported the synthesis of CoS x nanosheets from ionic liquid and applied it for the oxygen evolution reaction.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that when modeling HER on under-coordinated catalytic sites like a single atom, adsorption with more than one hydrogen should be carefully considered in order to avoid uncertainty in the theoretical conclusions. Better understanding of the HER mechanism is not only beneficial to N 2 and CO 2 reduction, but could also be beneficial in addressing the pressing challenges of hydrogen production and storage that the world faces [32][33][34][35][36]. Figure 1 shows the DFT-optimized structures of hydrogen adsorbed at a single atom site of a g-C 3 N 4 structure, using Os as an example.…”
Section: Introductionmentioning
confidence: 99%